Comparison of local stress based concepts — Effects of low-and high cycle fatigue and weld quality. (November 2015) - Stenberg, T.; Barsoum, Z.; Balawi, S.O.M.
Abstract: This paper presents a study of the ability for two stress based methods, the effective notch stress method and the structural stress approach, to estimate the fatigue life in the low cycle and the high cycle fatigue regime, considering the weld quality. Two different non-load carrying joint configurations were considered, cruciform joint and T-joint. The conducted fatigue analysis shows that both methods are capable to estimate the fatigue life with good accuracy within the low cycle and the high cycle regime. The effective notch stress generally shows a smaller scatter, it also considers increased weld quality with good accuracy, in contrast to the structural stress approach. Highlights: A comparison of local stress based concepts for fatigue assessment is made. The assessment is conducted using fatigue testing and numerical analysis. Local stress based concept shows good link between weld quality and fatigue life. Local stress based concept is capable of predicting low cycle fatigue behavior.